Приоритизация рисков информационной безопасности на основе нейро-нечеткой системы - Татаринова, Ю. Е. (ХНУРЕ, 2019)
The article is devoted to the process of vulnerability risk assessment of information systems with application of fuzzy set theory. It defines proposed model, which defines the set of linguistic variables and one output variable that describes degree of vulnerability exposure on target computer system. Linguistic variables characterize vulnerability information obtained from public resources. Base of rules and membership functions generated automatically by applying neuro fuzzy logic system.